Engagement with healthcare providers and healthcare system navigation among Australians with chronic conditions: a descriptive survey study. Issue 12 (9th December 2022) - Zurynski, Yvonne; Ellis, Louise A; Pomare, Chiara; Meulenbroeks, Isabelle; Gillespie, James; Root, Jo; Ansell, James; Holt, Joanna; Wells, Leanne; Braithwaite, Jeffrey
Abstract : Objectives: With the rate of chronic conditions increasing globally, it is important to understand whether people with chronic conditions have the capacity to find the right care and to effectively engage with healthcare providers to optimise health outcomes. We aimed to examine associations between care navigation, engagement with health providers and having a chronic health condition among Australian adults. Design and Setting: This is a cross-sectional, 39-item online survey including the navigation and engagement subscales of the Health Literacy Questionnaire, completed in December 2018, in Australia. Binary variables (low/high health literacy) were created for each item and navigation and engagement subscale scores. Logistic regression analyses (estimating ORs) determined the associations between having a chronic condition and the navigation and engagement scores, while controlling for age, gender, level of education and income. Participants: 1024 Australians aged 18–88 years (mean=46.6 years; 51% female) recruited from the general population. Results: Over half (n=605, 59.0%) of the respondents had a chronic condition, mostly back pain, mental disorders, arthritis and asthma. A greater proportion of respondents with chronic conditions had difficulty ensuring that healthcare providers understood their problems (32.2% vs 23.8%, p=0.003), having good discussions with their doctors (29.1% vs 23.5%, p=0.05), discussing things with healthcare providers until they understand all they needed (30.5% vs 24.5%, p=0.04), accessing needed healthcare providers (35.7% vs 29.7%, p=0.05), finding the right place to get healthcare services (36.3% vs 29.2%, p=0.02) and services they were entitled to (48.3% vs 40.6%, p=0.02), and working out what is the best healthcare for themselves (34.2% vs 27.7%, p=0.03). Participants with chronic conditions were 1.5 times more likely to have low scores on the engagement (adjusted OR=1.48, p=0.03, 95% CI 1.05 to 2.08) and navigation (adjusted OR=1.43, p=0.026, 95% CI 1.043 to 1.970) subscales after adjusting for age, gender, income and education. Conclusion: Upskilling in engagement and communication for healthcare providers and people with chronic conditions is needed. Codesigned, clearly articulated and accessible information about service entitlements and pathways through care should be made available to people with chronic conditions. Greater integration across health services, accessible shared health records and access to care coordinators may improve navigation and engagement.